Strategi Komunikasi Pemasaran PT Citiasia Internasional dalam Mengembangkan Aplikasi Inidesaku - Nida Nabila Putri; Jamiati KN (MUKASI: Jurnal Ilmu Komunikasi, 2023)
Indonesia has entered the digitalization era by utilizing technology. However, the gap in understanding between urban and rural communities is one of the obstacles to technological development in this country. PT Citiasia Internasional created the Inidesaku application which is aimed at building village communities so that they can compete in this era. In marketing the application, a marketing communication strategy is needed to achieve company goals. This made researchers interested in conducting research with the title "Marketing Communication Strategy of PT Citiasia Internasional in Developing Inidesaku Applications". The theory used is a marketing communication strategy by Kohler & Smith (Banjarnahor, et all, 2021), namely advertising, sales promotion, public relations & publicity, personal selling, direct marketing, sponsorship, corporate identity, packaging, point of sale & merchandising , as well as word of mouth. The results showed that PT Citiasia Internasional used 9 (nine) of 10 (ten) marketing communication strategies in accordance with the theory used. As for 1 (one) of 10 (ten) strategies that are not used is sponsorship, because it is not specifically on behalf of the Inidesaku application. The results of the study also state that personal selling (direct sales) is most effectively used in promoting the Inidesaku application to get clients.